2014
DOI: 10.4103/0377-4929.130905
|View full text |Cite
|
Sign up to set email alerts
|

Early dengue diagnosis by nonstructural protein 1 antigen detection: Rapid immunochromotography versus two the enzyme-linked immunosorbent assay kits

Abstract: Dengue is known for its serious life-threatening complications. New rapid kits available recently in India target circulating non-structural protein (NS1) antigen from day one onwards. The sensitivity and specificity of a newly introduced rapid combo kit against two conventional ELISA kits is assessed. The performance of this kit is quite satisfactory since excellent agreement of 94.26% was observed with particular reference to NS1 antigen detection among all three kits namely Rapid SD Bioline dengue Duo (SD K… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
11
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 0 publications
2
11
0
Order By: Relevance
“…Maximum seropositive patients 50 (55.56%) belonged to the age group of 15-45 years composed of young-working male population. Similar data was obtained by a study conducted by Stephen et al, 2014. The reactivity gradually decreased towards extremes of age group [ Table 1].…”
Section: Resultssupporting
confidence: 88%
“…Maximum seropositive patients 50 (55.56%) belonged to the age group of 15-45 years composed of young-working male population. Similar data was obtained by a study conducted by Stephen et al, 2014. The reactivity gradually decreased towards extremes of age group [ Table 1].…”
Section: Resultssupporting
confidence: 88%
“…Among these tests, the Panbio early dengue NS1 capture ELISA has shown to have an overall sensitivity of 60.4 to 66% and a specificity of 97.9 to 99% [10]-[12]. It has also been shown that NS1 rapid antigen detection tests (SD Diagnostics, Bioline, South Korea) has a [13] sensitivity of 81.6% and a specificity of 92% [14]. …”
Section: Introductionmentioning
confidence: 99%
“…In fact, the problem of false-negative in dengue diagnosis is an important issue for discussion. First, the problem of the NS1 assay in dengue diagnosis is noted worldwide 2 . Combining with other immunological test is suggested for improvement of diagnostic accuracy 2 .…”
mentioning
confidence: 99%
“…First, the problem of the NS1 assay in dengue diagnosis is noted worldwide 2 . Combining with other immunological test is suggested for improvement of diagnostic accuracy 2 . Also, it should be noted that the diagnosis of dengue in many tropical countries is usually a presumptive diagnosis without the laboratory confirmation 3 .…”
mentioning
confidence: 99%